2018
DOI: 10.1002/slct.201702541
|View full text |Cite
|
Sign up to set email alerts
|

Computational Unravelling of the Role of Alkyl Groups on the Host‐Guest Complexation of Pillar[5]arenes with Neutral Dihalobutanes

Abstract: Density Functional Theory (DFT) calculations have been carried out to understand the electronic structure and non-covalent interactions within host-guest complexes between 1,4-dihalobutanes (DHBs) and alkylated pillar[5]arenes (P5 A). Binding energies show that the propyl substituted P5 A are found to have greater binding abilities than that of P5 A with smaller alkyl chains. Among the halogens, dibromobutane is found to have higher binding energy compared to difluoro and dichloro butanes respectively. Contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Pillararene (in this instance 1,4-dimethoxypillar [5]arene) is afforded by reaction with boron trifluoride diethyl etherate in the presence of paraformaldehyde and can be fine-tunedbyi ncreasing ring expansion [37] and alteringt he functional groups at either rim. [38] Figure 5. Porous organic cage,CC3-R with tetrahedrally arranged windows.…”
Section: Metal-organic Polyhedramentioning
confidence: 99%
“…Pillararene (in this instance 1,4-dimethoxypillar [5]arene) is afforded by reaction with boron trifluoride diethyl etherate in the presence of paraformaldehyde and can be fine-tunedbyi ncreasing ring expansion [37] and alteringt he functional groups at either rim. [38] Figure 5. Porous organic cage,CC3-R with tetrahedrally arranged windows.…”
Section: Metal-organic Polyhedramentioning
confidence: 99%
“…To this direction, complexation of neutral 1,4-dihalobutanes with different alkyl pillar[5]­arenes were studied by Li and others . Computational investigations suggested that dispersive interactions accompanying guest penetration render large stability to such host–guest complexes . Noteworthy enough, EtP5 displays the strongest binding toward 1,4-diiodobutane than 1,4-difluorobutane.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained unambiguously indicate the formation of the 7/5-VT complex. The absence of cross peaks between 5-VT and aromatic protons of pillar [5]arene 7 indicates that the monomer is not in the macrocyclic cavity but in the pseudocavity of the macrocycle formed by fragments of substituents [62][63][64].…”
Section: Study Of the Interaction Of Pillar[5]arenes With Pvt And Pvte Polymersmentioning
confidence: 99%